1999
DOI: 10.1159/000018131
|View full text |Cite
|
Sign up to set email alerts
|

Mycosis fungoides with Mucinosis follicularis in Childhood

Abstract: Mycosis fungoides is a cutaneous T-cell lymphoma (CTCL) usually observed in mid to late adulthood. It occurs only rarely during childhood. Follicular mucinosis is a chronic dermatosis involving the sebaceous glands and outer root sheaths. It is normally differentiated into a juvenile benign form and an adult form possibly associated with mycosis fungoides. We report a 12-year-old boy who presented with an 8-month history of erythematous mucinous plaques on the scalp. Three months later, he developed erythemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 20 publications
(21 reference statements)
1
26
1
1
Order By: Relevance
“…El-Hoshy and Hashimoto [17]and Zackheim et al [18]reported a figure of about 6% of all cases of CTCL seen in reference centers, but the growing number of reports dealing with this issue would suggest that the right incidence might be higher. The clinical presentation of MF in this age is polymorphous ranging from classical MF [18], to the hypopigmented variant [17, 19], to pityriasis-lichenoides-like MF [20]and to cases presenting with the features of benign mucinosis follicularis [21]. …”
Section: Discussionmentioning
confidence: 99%
“…El-Hoshy and Hashimoto [17]and Zackheim et al [18]reported a figure of about 6% of all cases of CTCL seen in reference centers, but the growing number of reports dealing with this issue would suggest that the right incidence might be higher. The clinical presentation of MF in this age is polymorphous ranging from classical MF [18], to the hypopigmented variant [17, 19], to pityriasis-lichenoides-like MF [20]and to cases presenting with the features of benign mucinosis follicularis [21]. …”
Section: Discussionmentioning
confidence: 99%
“…4,[207][208][209] Two distinct types of alopecia mucinosa are traditionally recognized: primary idiopathic and secondary lymphoma-associated disease. 210 Because of considerable epidemiologic and clinicopathologic overlap between these 2 categories, [211][212][213][214][215][216] and reports of development of lymphoma in a number of cases of primary disease, 209,217,218 this distinction may be artificial and potentially misleading practically. Primary and secondary alopecia mucinosa may instead represent aspects of a disease spectrum, with primary alopecia mucinosa alternately viewed as a premalignant condition 219 or an indolent form of follicular mycosis fungoides (MF) outright, with an excellent prognosis.…”
Section: Alopecia Mucinosamentioning
confidence: 99%
“…They are rare in childhood [2]. The largest group of cutaneous lymphomas (about 65%) are those originating from T cells, and the most common diseases of this group are mycosis fungoides (MF), which has a relatively good prognosis [3], and the more aggressive leukemic variant Sézary syndrome.…”
Section: Introductionmentioning
confidence: 99%